Innovation, Preparation of Cephalexin Drug Derivatives and Studying of (Toxicity & Resistance of Infection) - Jawad , Dr. Aseel Mahmood (International Journal of Psychosocial Rehabilitation, 2020)
The current study developed new drugs and new pharmaceutical derivatives against infection and toxicity via Invention and preparation of medication through various chemical reactions and bio-medical studies to improve its efficiency which involved study of resistance of infection and toxicity effect. The invented Cephalexin derivatives have been prepared through many reactions with many steps, which identified through several techniques represented by (Infrared spectra, carbon and proton magnetic resonance)– spectrophotometric identification methods, then bio- medical studying via several experiment in this field like cytotoxicity, resistance of bacteria.